Ocular Toxocariasis Presenting as Endophthalmitis in a Young Adult Intravenous Drug User. (March 2021) - Singh, Pali P.; Robbins, Cason B.; Feng, Henry L.; Borkar, Durga S.; Fekrat, Sharon
Purpose: This report describes the diagnosis of ocular toxocariasis presenting as endophthalmitis in an adult intravenous drug user. Methods: A case is reported. Results: Fundus imaging showed numerous white opacities obscuring the macula. Toxocara canis serology was reactive with an enzyme immunoassay titer of 1:2 (positive ≥ 1:32). Findings from bacterial and fungal cultures were negative, and vitrectomy cytology revealed no organisms. Postoperatively, serial optical coherence tomography imaging demonstrated a slight decrease in size of an intraretinal hyperreflective lesion in the macula. Conclusions: Owing to a variety of presentations, ocular toxocariasis can be challenging to diagnose. In a patient with a history of intravenous drug use where fungal and bacterial organisms are more common causes of endophthalmitis, it is important to have a wide differential of causative organisms, particularly in the context of negative culture results and a worsening clinical examination.